Partisipasi Masyarakat Dalam Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) di Kecamatan Simpur Kabupaten Hulu Sungai Selatan - Afriadi, Taufik; Wahyono, Hadi (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
The study examines the gap between expectations and realization of PAMSIMAS (Program`Air Minum dan Sanitasi Berbasis Masyarakat – Community Based Drinking Water and Sanitation Program) in Simpur District, Hulu Sungai Selatan Regency in Borneo, which has been implemented starting in 2008 in three villages, namely Garunggung, Ulin and Pantai Ulin. However, Garunggung and Ulin have also received Village Incentive Grant (Hibah Insentif Desa – HID) from the government, and Pantai Ulin has not. The study focuses on the level of participation of the people, comparing the villages having received the HID and those not. The study found differences in planning, implementation, as well as operation and maintenance of the PAMSIMAS in the villages having received HID and those not. For example the study found differences in planning in terms of interference from stakeholders and accommodation of interests. Education and occupation have become the dominant factor affecting participation level. Education influences knowledge and awareness, while occupation, having close connection to income, influences the availability of time to participate.